Waste-to-wealth : American bullfrog skin-derived collagen for wound dressing applications - Cimenoglu, Cigdem (Nanyang Technological University, 2021)
Wound healing is a complex process in which four successive steps involve along with various cell types, extracellular matrix proteins and growth factors. Successful wound healing process is highly dependent on the completion of each step, and many complications could be developed due to the complexity. Therefore, all-inclusive interactive wound dressings produced using collagen as an active compound have been extensively studied and applied in clinical applications. The majority of collagen-based wound dressings are fabricated from mammalian-derived collagen, which could potentially possess various risks such as disease transmission and allergic reaction as well as religious restrictions. In addition, the high production cost of mammalian-derived collagen-based products discourages the use in wound healing applications. Therefore, in the recent years, marine-derived collagen as an alternative source of collagen in wound healing application has been explored albeit its low extraction yield and low thermal stability which hinders the scale-up production and the applicability. In this regard, there is a necessity to investigate an alternative non-mammalian source of collagen with higher thermal stability and a more cost-effective production process.